PENGARUH MUTASI KERJA TERHADAP KINERJA APARAT DI KEPOLISIAN RESORT BANTAENG - Wahyuni, Dwi; Adys, Abdul Kadir; Yusuf, Muhammad (Universitas Muhammadiyah Makassar, 2024)
The purpose of this study is to determine the effect of job rotation on the performance of Bantaeng Resort Police officers. The performance of officers is influenced by several factors, one of which is job rotation. Proper and directed job rotation can improve officer performance. This study uses a descriptive quantitative and associative esearch method, utilizing a questionnaire as an instrument. The sampling technique used in this study is total sampling, targeting Bantaeng Resort Police officers with a sample size of 22 individuals. The data collection techniques used are observation, questionnaires, and documentation. The data analysis technique employs simple linear regression analysis. Data validity is ensured through validity and reliability tests. The results of this study show that job rotation has an effect on the performance of Bantaeng Resort Police officers. Based on the output from the model summary, the R value obtained is 0.821, indicating the influence of the independent variable, job rotation (X), on the dependent variable, officer performance (Y), which is further strengthened by the coefficient of determination (R Square) or its determination coefficient of 0.674 or 67.4%. Keywords: Job Rotation, Officer Performance